2013
DOI: 10.1007/s10640-013-9644-0
|View full text |Cite|
|
Sign up to set email alerts
|

Willingness to Pay and Sensitivity to Time Framing: A Theoretical Analysis and an Application on Car Safety

Abstract: Stated preference (SP) surveys attempt to obtain monetary values for non-market goods that reflect individuals' "true" preferences. Numerous empirical studies suggest that monetary values from SP studies are sensitive to survey design and so may not reflect respondents' true preferences. This study examines the effect of time framing on respondents' willingness to pay (WTP) for car safety. We explore how WTP per unit risk reduction depends on the time period over which respondents pay and face reduced risk in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…Hammitt and Haninger (2007) found the estimated value of risk reduction not to be sensitive to the time framing. Andersson et al (2011) found WTP per unit risk reduction to be sensitive to time framing with the annual scenario producing WTP estimates that were 70% larger than in the monthly scenario, a result that is likely to be driven by sensitivity to the framing of the risk reduction more than sensitivity to the frequency of payment.Further, it is not uncommon for studies to introduce a binary response question prior to the PC question (see for example Langford et al, 1998). The impact of introducing a binary response question where respondents are asked to indicate whether they are at all willing to pay for good prior to a PC follow-up has to the authors knowledge not been tested in previous studies.The good being evaluated in the present study is ambulance helicopter service.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Hammitt and Haninger (2007) found the estimated value of risk reduction not to be sensitive to the time framing. Andersson et al (2011) found WTP per unit risk reduction to be sensitive to time framing with the annual scenario producing WTP estimates that were 70% larger than in the monthly scenario, a result that is likely to be driven by sensitivity to the framing of the risk reduction more than sensitivity to the frequency of payment.Further, it is not uncommon for studies to introduce a binary response question prior to the PC question (see for example Langford et al, 1998). The impact of introducing a binary response question where respondents are asked to indicate whether they are at all willing to pay for good prior to a PC follow-up has to the authors knowledge not been tested in previous studies.The good being evaluated in the present study is ambulance helicopter service.…”
mentioning
confidence: 95%
“…Andersson et al . () found WTP per unit risk reduction to be sensitive to time framing with the annual scenario producing WTP estimates that were 70% larger than in the monthly scenario, a result that is likely to be driven by sensitivity to the framing of the risk reduction more than sensitivity to the frequency of payment.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of dichotomous choice CV surveys include Andersson et al, 2014, Cunha-e-Sa et al (2012, Evans et al (2011), Herriges et al (2010) and McConnell (1990). Proposed environmental benefits are typically long lasting, but researchers sometimes present survey respondents with a one-time payment or a series of annual installments spread over a few years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, both approaches were implemented to analyze WTP responses, which is a common practice in CV literature (e.g. Hutchinson et al, 2001;Crooker and Herriges, 2004;Andersson et al, 2013).…”
Section: Parametric and Non-parametric Models To Estimate Households'mentioning
confidence: 99%